2015
DOI: 10.1016/j.gdata.2015.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of rice seedlings in response to glutamine treatment

Abstract: Glutamine, the most abundant free amino acid in humans (Curi et al., 2007 [1]), has many functions. In addition to protein, amino acid, and nucleic acid biosynthesis, glutamine also regulates the expression of genes related to metabolism, cell defense, and signal transduction in humans (Curi et al., 2007 [1]; Brasse-Lagnel et al., 2009 [2]). Glutamine is also one of the major forms of nitrogen in rice (Fukumorita and Chino, 1982 [3]). In addition to metabolic and nutritional effects, glutamine may function as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…We have previously shown that glutamine can effectively support rice seedling growth when supplemented as the sole nitrogen source in hydroponics [ 33 ]. In addition to its role in plant nutrition, glutamine can rapidly induce the expression of key transcription factor genes involved in nitrogen and stress responses in rice roots [ 33 , 34 ]. These findings support the notion that amino acid signaling pathways may crosstalk with biotic and abiotic signaling networks in plants.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that glutamine can effectively support rice seedling growth when supplemented as the sole nitrogen source in hydroponics [ 33 ]. In addition to its role in plant nutrition, glutamine can rapidly induce the expression of key transcription factor genes involved in nitrogen and stress responses in rice roots [ 33 , 34 ]. These findings support the notion that amino acid signaling pathways may crosstalk with biotic and abiotic signaling networks in plants.…”
Section: Introductionmentioning
confidence: 99%
“…When Gln was administered to maize seedlings via tip-cut leaves, root N uptake was shown to decrease [37]. In addition to transporter regulation, increased Gln was shown to control at least 35 general stress response genes in rice [39,40]. Increased Gln has also been implicated in coordinating sulphate and N nutrition in barley [41], and to exert control over the C4 photosynthetic pathway in maize [42].…”
Section: Implications Of a Limited Gln-availability Period In Maize Lmentioning
confidence: 99%